The internet: host to diverse new species of businesses. (1st January 2002) - McNamee, Patrick B.; O'Reilly, Dolores; Jordan, Liam
This paper examines in an innovative way some of the profound effects that the internet is having and is likely to have on business in the future. Using the biological analogy that in nature unique new niches support unique new forms of life, so, it argues, in the business world when there is a strategic discontinuity, unique new business niches develop and then support new types of firms. In the paper, the new business niche is the internet and the new types of companies it supports are the web page designers. A feature of the paper is that it uses a specially constructed web page on the internet to survey web page design companies. These companies were surveyed to ascertain their ownership, structure strategies and performance. Thus, this is a new approach to survey analysis the use of the internet for interactive survey research.